Effectiveness of Nursing Guidelines on Marital Outcomes of Women with Urinary Incontinence - Samia G. Gouda; Nadia M. Fahmy; Hanan A. F. Mahjoub; Nadia A. Attia Allah (Evidence-Based Nursing Research)
Context: Urinary incontinence is an important multifactorial health problem that affects women's life quality negatively and is related significantly to age, education, occupation, marital status, and body mass index.